(untitled) (Polis (Santiago), 2018)
For the author of this article, research is to produce a new knowledge from a certain reality, but cautions that this research is marked by who determines the limits and scope, such as the definition of their object of research, techniques used, analysis criteria, and even how to write and present their findings and conclusions. For the researcher will have independence, it must be said to be attentive to how much of himself in that job is yours. But the dilemmas are compounded when research is commissioned, and there are ethical and epistemological issues discussed in this paper.